Inequality of Fuzzy Soft κ Quasi-Hyponormal Operator Formulated Along with Several Analytic Features - Mohsen, Salim Dawood (Iraqi Journal of Science, 2025)
Fuzzy soft operator theory (FS-OT) is the connection between operator theory and fuzzy theory that has recently been raised and discussed, which has a central significant role in the evolution of functional analysis. In this sequel, a new general class of fuzzy soft operators on fuzzy soft Hilbert space (FS-H) are introduced, called fuzzy soft κ quasi-hyponormal operators. These operators are generalized fuzzy soft hyponormal operators. Then, a sufficiently equivalent major condition for these imposed operators called feature characterization is achieved. Besides, several interesting features of quasi-hyponormal operators are yielded along with other outcomes. Therefore, conditions concerning the achieving of those analytical features are also investigated.